Self-metalation of monophosphonic acid tetraphenylporphyrin on TiO2(110)-(1×1) - Fernández, Cynthia C.; Wechsler, Daniel; Lytken, Ole; Steinrück, Hans-Peter; Williams, Federico J. (Surface Science, 2022)
Fundamental studies on the interaction of porphyrin molecules with oxide surfaces are important due to the relevance of these systems in emerging technologies. In this work, we used X-ray photoelectron spectroscopy (XPS) to study the interaction of solution-deposited monophosphonic acid tetraphenylporphyrin (MPTPP) molecules with well-defined rutile TiO2(110)-(1×1) surfaces as a function of coverage and temperature. We found that molecules adsorb mainly in their free-base form with some molecules protonating on the surface at room temperature. In agreement with the behavior of carboxylic acid functionalized porphyrin molecules, raising the temperature results in porphyrin self-metalation and the temperature onset for self-metalation shifts to higher values as the coverage is increased. Furthermore, we found that self-metalation is accompanied by surface reduction, and we propose a mechanism based on the formation of oxygen vacancies driven by water desorption. Our findings contribute towards the understanding of the rich surface chemistry that porphyrin molecules have on oxide surfaces.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Porphyrin molecules; Self-metalation; TiO